The development of strategic deoxygenation of seed oil for bio-energy use - Pedzisai, Standford Mirainashe (My University, 2022)
The growing demand for diesel fuel in the face of the rapidly dwindling fossil fuel reserves, oil price fluctuations and stringent pollution control regulations has stimulated the growth of the biofuels industry, particularly biodiesel production as it is presently the best commercially produced renewable alternative to petroleum diesel. Biodiesel is a recognized complement and credible replacement of mineral diesel with overwhelming attributes relative to fossil diesel such as eco-friendliness, non-toxicity and good lubricity when used in diesel engines. Biodiesel is popularly produced as Fatty Acid Alkyl Esters through catalytic transesterification of triglycerides with an alkyl donor. However, Fatty Acid Alkyl Esters have limitations in oxidation stability, calorific value and cold flow properties relative to mineral diesel hence are throttled in their blending ratios with the latter to prevent engine damage and power losses during engine operation. The alternative renewable diesel synthesis strategy, deoxygenation, which yields n-alkanes and nalkenes from fatty acids and triglycerides, produces better quality renewable diesel which can be employed in the currently existing engines at higher blending proportions or in its pure form without the aforementioned FAAEs problems. However, for this strategy to be economically viable for industrial scale production, there exists a need for its optimization with regards to the operating parameters and the diversity of the feedstock oils. The deoxygenation of waste cooking oil was optimized using Design Expert® and the optimum conditions were applied on castor oil to investigate the influence of oil composition on its deoxygenation success. Five bimetallic catalysts of varying Ni: Co ratios were synthesized by impregnation to an alumina support. The optimum Ni:Co composition ratio for the catalyst was found to be 1:1 based on its selectivity for the deoxygenation of waste cooking oil. Various characterization techniques were employed to investigate the effects of catalyst composition on its physiochemical properties. The GC-MS was used for the characterization of the oils used in this work. Deoxygenation activity was discovered to be having a directly proportional relationship with reaction time, temperature and catalyst loading influence although to different magnitudes. Oil composition was also discovered to have considerable influence on the rate and extent of its deoxygenation. It was deduced therefore that catalysts behave differently with different oils. The highest deoxygenation extent for waste cooking oil (96.12%) was realized for the reaction conditions: 1Ni:1Co/Al2O3 catalyst, 300°C reaction temperature, 5 hours reaction duration, and a catalyst loading of 1 wt.%. Under the same reaction conditions, a 37.4% oxygen content reduction from castor oil was realized.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and Built Environment, University of Witwatersrand, Johannesburg, 2021